Why a playwork perspective on play suits a qualitative research paradigm - Peter King (Handbook of Qualitative Research in Education, 2020)
Playwork is a new and developing profession with an increase in empirical research. This chapter considers how playwork research on play suits a qualitative paradigm considering four factors: rights-based, process, critical-reflection and playfulness.